Cost-effectiveness of a technology based health intervention module on under-five childhood immunization schedule - Rusli, Mohammad Farhan; Mohd Zulkefli, Nor Afiah; Juni, Muhamad Hanafiah (Universiti Putra Malaysia, 2018)
Technology based health intervention has seen an increase in use in multiple health programs. Improving non-adherence days ensures that children achieve maximum benefits of the immunization program. Determining the cost-effectiveness of the intervention to improve non-adherence days to the under-five childhood immunization schedule will be beneficial to policy and decision makers. A quasi-experimental study was conducted in nurseries in Putrajaya and Cyberjaya from January 2016 to January 2018. The sample size were 196 respondents with Putrajaya as the intervention group and Cyberjaya as the wait-listed control group. The intervention was a technology based health education module. Intervention groups received the intervention through the messaging service of Whatsapp at pre-determined intervals. Respondents answered a validated, self-administered questionnaire at baseline, immediately post-intervention and 3 months post-intervention. The costs of this program was then calculated to determine its cost-effectiveness. Data was analysed using Statistical Package for Social Science (SPSS) Version 23. The mean non-adherence days were 10 at baseline with no significant difference between both groups. The cost-effectiveness analysis showed that the intervention was cost effective with the cost-effectiveness ratio being less than 1. The technology based health intervention module was cost-effective in improving non-adherence days. The ability to improve non-adherence will greatly benefit children who receive the under-five childhood immunizations and the costs reduction may help policy makers to determine future plans of action.